On some reciprocal relations between the factors of the upper and lower central series in Lie algebras - Kurdachenko, L.A.; Pypka, A.A.; Subbotin, I.Ya. (Reports of the National Academy of Sciences of Ukraine, 2015)
A generalization of the group-theoretic Baer's theorem regarding relations between the factors of the upper and lower central series for Lie algebras is obtained.